The measurement of carotid intima media thickness precisely and accurately for evaluating epilectic children treated with oxcarbazepine - Inci, Mehmet Fatih; Ozkan, Fuat; Demir, Caner Feyzi (Elsevier Science Bv, 2013)
[Abstract Not Available]
Keywords: Risk